2008
DOI: 10.1016/j.cardfail.2008.07.188
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Signs and Symptoms During Hospitalization for Acute Heart Failure Follow Different Patterns and Depend on the Measurement Scales Used: An International, Prospective Registry to Evaluate the Evolution of Measures of Disease Severity in Acute Heart Failure (MEASURE-AHF)

Abstract: Background The natural evolution of signs and symptoms during acute heart failure (AHF) is poorly characterized. Methods and Results We followed a prospective international cohort of 182 patients hospitalized with AHF. Patient-reported dyspnea and general well-being (GWB) were measured daily using 7-tier Likert (–3 to +3) and visual analog scales (VAS, 0–100). Physician assessments were also recorded daily. Mean age was 69 years and 68% had ejection fraction <40%. Likert measures of dyspnea initially improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 34 publications
2
31
1
Order By: Relevance
“…25 In the Initiation Management Pre-discharge Assessment of Carvedilol Therapy in Heart Failure registry, the degree of weight loss during hospitalization for ADHF was not associated with the degree of improvement in dyspnea at rest. 26 The MEASURE-AHF registry 27 and the PROTECT pilot study 9 also reported that changes in body weight were not related to changes in symptoms. By contrast, in the Efficacy of Vasopressin Antagonism in Heart Failure Outcome Study With Tolvaptan (EVEREST) trial, reductions in body weight in response to tolvaptan on day 1 were accompanied by significant improvements in patient-assessed dyspnea.…”
Section: Discussionmentioning
confidence: 99%
“…25 In the Initiation Management Pre-discharge Assessment of Carvedilol Therapy in Heart Failure registry, the degree of weight loss during hospitalization for ADHF was not associated with the degree of improvement in dyspnea at rest. 26 The MEASURE-AHF registry 27 and the PROTECT pilot study 9 also reported that changes in body weight were not related to changes in symptoms. By contrast, in the Efficacy of Vasopressin Antagonism in Heart Failure Outcome Study With Tolvaptan (EVEREST) trial, reductions in body weight in response to tolvaptan on day 1 were accompanied by significant improvements in patient-assessed dyspnea.…”
Section: Discussionmentioning
confidence: 99%
“…6 Past studies demonstrate that the VAS better captures changes in dyspnea over time compared to Likert-type scales, and that patient positioning during measurement (sitting upright vs. supine) affects responses. 5,7 Timing of dyspnea assessment is also important, as earlier treatment is associated with greater dyspnea relief, although many patients remain symptomatic despite early therapeutic intervention. 3,4,8,9,10 Early dyspnea relief has also been associated with improved 30-day outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several efforts have been made to evaluate the evolution of symptoms in AHFS, the relative change in various instruments compared with each other, and the association of such changes with other outcomes. 46,47 A recent proposal for standardized dyspnea assessment is an important first step toward better application of patient reported outcomes in clinical trails in AHFS. 48 As with breathlessness, the evaluation of congestion is dependent on relatively qualitative measures (jugular venous pressure, peripheral edema, rales, congestion on chest radiograph) that may not be highly correlated with more objective measures.…”
Section: Study Design: Methodological Issues In Ahfs Clinical Trialsmentioning
confidence: 99%